Comparison of Service Quality, Price, and Physical Evidence of RG Fried Chicken and Richeese Factory on Millennial Generation and Gen Z in Pekanbaru City - Elviani, Rahma; Berampu, Lailan Tawila; Wildah, Sri Wahyuni; Noviasari, Henni (Economics, Business and Management Science Journal, 2026)
This study aims to compare the service quality, price, and physical evidence between local and national fast food restaurants in Pekanbaru City, specifically RG Fried Chicken and Richeese Factory, among Millennial and Gen Z consumers. A quantitative approach was used with data collection through questionnaires distributed to respondents who had made purchases at both restaurants. The data were analyzed using descriptive analysis and hypothesis testing with the Paired Sample t-Test method assisted by SPSS version 21 to test the differences between the two research objects. The results showed that there was no significant difference in service quality among Millennials, while there was a significant difference among Generation Z. In addition, there was a significant difference in physical evidence for both generations. However, no significant difference was found in the price variable among Millennials, while a significant difference was found among Generation Z. These findings indicate that generational characteristics influence consumer perceptions of service quality, price, and physical evidence at local and national fast food restaurants in Pekanbaru City and in similar urban markets in Indonesia.